Solving Vendor Selection Problem by Interval Approximation of Piecewise Quadratic Fuzzy Number - Abd El-Wahed Khalifa, Hamiden; Bozanic, Darko; Saberi Najafi, Hashem; Kumar, Pavan (Optimality, 2024)
In this paper, a Vendor Selection Problem (VSP) with fuzzy parameter uncertainty is introduced. The buyer gives a quantity order for a commodity among a set of suppliers. Buyer’s objective is to obtain the requirements of lead time, service level and aggregate quality at the minimum cost. Some of the problem parameters are characterized by the piecewise quadratic fuzzy numbers. In addition, an interval approximation for piecewise quadratic fuzzy numbers is proposed for solving the VSP. The VSP with close interval approximation is approached by taking the minimum and maximum values inequalities with the constraints transformed it to two classical Linear Programming Problems (LPPs). The optimal solution for these LPPs is obtained. A numerical example is provided for illustration of the suggested approach.